Engineering processive DNA polymerases with maximum benefit at minimum cost - Reha-Krantz, Linda J.; Woodgate, Sandra; Goodman, Myron F. (Frontiers in Microbiology, 2014)
DNA polymerases need to be engineered to achieve optimal performance for biotechnological applications, which often require high fidelity replication when using modified nucleotides and when replicating difficult DNA sequences. These tasks are achieved for the bacteriophage T4 DNA polymerase by replacing leucine with methionine in the highly conserved Motif A sequence (L412M). The costs are minimal. Although base substitution errors increase moderately, accuracy is maintained for templates with mono- and dinucleotide repeats and replication efficiency is enhanced . The L412M substitution increases intrinsic processivity and the additions of phage T4 clamp and single-stranded DNA binding proteins further strengthen the ability of the phage T4 L412M-DNA polymerase to replicate all types of difficult DNA sequences. Increased pyrophosphorolysis is a drawback of increased processivity, but pyrophosphorolysis is curbed by adding an inorganic pyrophosphatase or divalent metal cations, Mn2+ or Ca2+. In the absence of pyrophosphorolysis inhibitors, the T4 L412M-DNA polymerase catalyzed sequence-dependent pyrophosphorolysis under DNA sequencing conditions. These pyrophosphorolysis-sensitive DNA sequences provide insights into how the T4 DNA polymerase switches between nucleotide incorporation, pyrophosphorolysis and proofreading pathways. The L-to-M substitution was also tested in the yeast DNA polymerases delta and alpha. Because the mutant DNA polymerases displayed similar characteristics, we propose that amino acid substitutions in Motif A have the potential to increase processivity and to enhance performance in biotechnological applications. An underlying theme in this chapter is the use of genetic methods to identify mutant DNA polymerases with potential for use in current and future biotechnological applications.